Evaluasi Mutu Alat Komunikasi Polri dan Penggelarannya untuk Mendukung Pelaksanaan Tugas Kepolisian dalam Rangka Pengamanan Pemilu 2024: Evaluasi Mutu Alat Komunikasi Polri dan Penggelarannya untuk Mendukung Pelaksanaan Tugas Kepolisian dalam Rangka Pengamanan Pemilu 2024 - Raslin, Harvin (Jurnal Litbang Polri, 2024)
General elections are a fundamental pillar of Indonesia's democratic system, conducted periodically. Each stage of the elections holds the potential to disrupt public safety and order with varying degrees of escalation. The Indonesian National Police (Polri), as the frontline guardian of the electoral process, faces significant challenges in ensuring its security. Chief of the Indonesian National Police, General Listyo Sigit Prabowo,M.Si. supports precision policing by planning the security for the 2024 general elections and regional elections (Pilkada) through budget allocation, personnel deployment, as well as facilities and infrastructure. In the context of facilities and infrastructure, Polri's radio communication equipment becomes one of the operational support systems for Polri in securing upcoming elections. Through a comprehensive, reliable, and effective communication network, along with suitable communication devices, Polri is able to carry out its tasks more efficiently and swiftly. This research aims to identify and analyze the quality of the currently deployed Polri radio communication equipment, as well as to analyze the conditions, quantity, and functions of its deployment. The methods used involve both qualitative and quantitative approaches, with data collected through in-depth interviews, observations, checklists, and questionnaires. The research findings reveal that the distributed Polri radio communication equipment across 10 regional police departments (Polda) consists of both conventional and trunking communication systems. From technological and security aspects, Polri's radio communication equipment has adequately met operational requirements, providing support for security and operational tasks. However, challenges exist in the form of malfunctions in Handy Talky devices and repeaters. Furthermore, in operating the communication equipment, there are deficiencies in knowledge, experience, and maintenance. Administrative constraints and the availability of spare parts also need attention in the maintenance of Polri's radio communication equipment.